Handbook of paleoanthropology - Henke, Winfried; Tattersall, Ian (Springer Berlin Heidelberg Imprint: Springer, 2015)
This extensive, three-volume handbook, intensively updated and enlarged, is a superb new resource for students, researchers, and practitioners in paleoanthropology. A baseline storehouse covering the full extent of current knowledge, the volume features an online e-reference work that will be updated with future developments in this fascinating discipline. Often cited as the most multidisciplinary of all the sciences, paleoanthropology encompasses a vast range of techniques drawn from geology, evolutionary biology, and archaeology, among many others.   Guided by an editorial team of global stature, the contributions reflect the best of today's scholarship. Each volume covers core constituents of the subject: basic principles and methods, primate evolution and human origins, and the phylogeny of hominins. The editors have ensured that the entries uphold a key principle of paleoanthropology, requiring historical assessments to be updated with developing knowledge of the living world. The handbook's first volume incorporates the enormous advances made in such areas as phylogenetic analysis, paleoecology and evolutionary theory and philosophy. Volume II integrates primate fossil data with the vast amount that is now known of the behavior and ecology of living primates in natural environments. The third volume deals with the fossil and molecular evidence for the evolution of Homo sapiens and its fossil relatives. Paleoanthropology is characterized by its many live and unresolved academic debates, which are reflected in the heterogeneity of intellectual standpoints in this handbook. This planned diversity ensures that the Springer Handbook of Paleoanthropology is a multilayered, comprehensive companion of inestimable value to students, academics, and working professionals alike.